EP254 The prognostic value of lymph node ratio in stage IIIC cervical cancer patients triaged to primary treatment by radical hysterectomy with systematic pelvic and para-aortic lymphadenectomy: a retrospective, dual-institutional study. (1st November 2019) - Aslan, K; Meydanli, MM; Oz, M; Tohma, YA; Haberal, A; Ayhan, A
Abstract : Introduction/Background: The aim of this study was to determine the prognostic value of lymph node ratio (LNR) in women with 2018 FIGO stage IIIC cervical cancer. Methodology: In this retrospective dual-institutional study, a total of 185 node-positive cervical cancer patients who had undergone radical hysterectomy with systematic pelvic and para-aortic lymphadenectomy were included. All of the patients received adjuvant chemoradiation after surgery. LNR was defined as the ratio of positive lymph nodes to the total number of lymph nodes removed. The patients were categorized into two groups according to LNR; LNR <0.05 and LNR≥0.05. The prognostic value of LNR was evaluated with univariate log-rank tests and multivariate Cox regression models. Results: A total of 139 patients (75.1%) had stage IIIC1 disease and 46 (24.9%) patients had stage IIIC2 disease. With a median follow-up period of 45.5 months (range 3–135 months), the 5-year disease free survival (DFS) rate was 62.5% whereas the 5-year overall survival (OS) rate was 70.4% for the entire study population. The 5-year DFS rates for LNR <0.05 and LNR ≥0.05 were 78.2%, and 48.4%, respectively (p<0.001). Additionally, the 5-year OS rates for LNR <0.05 and LNR ≥0.05 were 80.6%, and 61.2%, respectively (p=0.007). On multivariate analysis, LNR ≥0.05 was associated with a worse DFS (HR 2.13, 95% CI 1.21–3.72; p=0.008) and OS (HR 1.95, 95% CI 1.01–3.37; p=0.04) in women with stage IIIC cervical cancer. Conclusion: LNR ≥0.05 seems to be an independent prognostic factor for decreased DFS and OS in stage IIIC cervical carcinoma. Disclosure: Nothing to disclose.